GAMES ONLINE DAN PEMEROLEHAN BAHASA PADA ANAK: KAJIAN LITERATUR - Azizah Khoirunnisa; Beatrice Callista Prase Tjia; Faridz Muhammad Sidiq; Khayyirah Syifa Nurkhalisah; Muhammad Yazid Ulwan (Universitas Warmadewa, 2025)
A qualitative approach method was used to write this article and information was gathered through literature review. The information obtained is then analyzed using qualitative content analysis methods in order to obtain data that is in accordance with the overall context of the article. This article is written to discuss some of the research that has been done related to the influence of online games on language acquisition and aims to uncover vocabulary obtained and confirm the factors that influence language acquisition. The conclusion obtained is that children are able to obtain some foreign words from playing online games, but children also have the potential to acquire vulgar words and use them without knowing the context of the whole word. The length of words, the frequency of word repetition, and the meaningfulness of words are factors that affect the process of acquiring children's language.